THE ROLE OF TEACHERS IN IMPROVING DIGITAL LITERACY AND ETHICAL USE OF SOCIAL MEDIA AMONG STUDENTS: A LITERATURE REVIEW - Toto Heriyanto; Parni Parni (CV. ADIBA AISHA AMIRA, 2025)
This study aims to discuss the central role of teachers in improving digital literacy and instilling ethical social media use among students through a literature review. Digital transformation has required teachers to not only master technological competencies but also integrate them creatively into the learning process. Teachers act as facilitators, mentors, and role models in shaping students' digital character, including guiding students to behave wisely and responsibly when using social media. Teachers' efforts include integrating digital literacy into the curriculum, providing training on social media ethics, fostering critical thinking towards information, and collaborating with parents and the school community. This study uses a literature review method by analysing literature related to the role of teachers, digital literacy strategies, and social media ethics education. The results of the review indicate that the success of digital literacy and social media ethics is greatly influenced by the capacity, innovation, and leadership of teachers. Thus, teachers are the key to creating a generation of students who are digitally literate and ethical in the virtual world.